ORGANIZATIONAL AND ECONOMIC COMPONENTS OF ELECTRICAL GRIDS DEVELOPMENT PROGRAMS - SHASHKOV, Serhiy; ZUBKO, Vladyslav; CHEPIZHNYI, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the article researched the indicators that directly depend on the state of electrical networks. The first of them is the level of reliability of electricity supply, the indicators of which are the SAIDI and SAIFI indices. The domestic indicators of the specified indices significantly exceed the level in the countries of the European Union and to date have no signs of a decrease. Plans for reducing the indicator SAIDI have been analyzed in relation to the method of incentive tariffs for operators of distribution systems. The next considered indicator is high technological losses of electrical energy. It was analyzed that the volume of these losses has a growing trend and also significantly exceeds the average European level. The main reason for these phenomena is the outdated and worn-out condition of electrical grids, which, given the damage caused by missile strikes and shelling, tends to worsen. Proposals have been identified that in the future may help improve the condition of grids and eliminate a number of problematic phenomena Their main problems and approximate volumes of priority grids modernization were summarized. Possible practical measures aimed at helping to reduce technological losses of electricity are considered. The structure of the proposed traditional measures necessary to manage the development of networks and consumers were analyzed. It has also recently started in Ukraine development and approval of a set of documents which are directed to the implementation of the Energy Transition scenario and the implementation of the Smart Grid concept. The further need for the development of system and program documents at both the state and regional levels was identified. It is proposed to include in these documents a number of organizational and economic components which will most effectively contribute to the achievement of the set goals.